## Ask AI on The Internet

Question: The first term is 2 and the second term 1. The rest of the terms are found by multiplying the two terms before it together, and doubling the answer. 1st term= 2 2nd term= 1 3rd term= ........ 4th term= ........... 5th term= ..........

Given the sequence where each term is found by multiplying the two preceding terms together and then doubling the result, let's find the requested terms. 1. **First term \( a_1 \) = 2** 2. **Second term \( a_2 \) = 1** Using the given rule: \[ a_{n} = 2 \times (a_{n-1} \times a_{n-2}) \] We can find the subsequent terms as follows: **Third term \( a_3 \):** \[ a_3 = 2 \times (a_2 \times a_1) = 2 \times (1 \times 2) = 2 \times 2 = 4 \] **Fourth term \( a_4 \):** \[ a_4 = 2 \times (a_3 \times a_2) = 2 \times (4 \times 1) = 2 \times 4 = 8 \] **Fifth term \( a_5 \):** \[ a_5 = 2 \times (a_4 \times a_3) = 2 \times (8 \times 4) = 2 \times 32 = 64 \] So, the terms are: 1. \( a_1 = 2 \) 2. \( a_2 = 1 \) 3. \( a_3 = 4 \) 4. \( a_4 = 8 \) 5. \( a_5 = 64 \)

##### Think your answer is better than the AI's? Post it below.

##### Other Most Relevant Posts:

##### Question Tags

If you want your question answered by an AI, click here.

## Post your own comment: